ANALYSIS OF ORGANIC COMPOUNDS IN WATER SAMPLES BY SOLID PHASE EXTRACTION METHOD (SPE) COLUMN C8 - VANIA SOFYAN (NIM : 10509061) ; Pembimbing, Prof. Dr. Buchari, FEBI
Analysis of organic compounds in water samples was performed using Solid Phase Extraction (SPE) method column C8. Solid phase extraction method or SPE is not only used to eliminate matrix, but also to increase the concentration of the water samples. Water sampling was conducted in two areas, the first area is Citarum River which is located in Batujajar (Batujajar 1 and Batujajar 2) and the second area was in Saguling Lake. The physical parameters, temperature, Total Suspended Solid (TSS), Total Dissolve Solid (TDS), and conductivity of water, were measured and the chemical parameter in water such as pH was also measured. The temperature of Citarum River was 26 oC and Saguling Lake was 27 oC. The conductivity values of water sample in Citarum River was 11,6 μS (Batujajar 1) and 11,0 μS (Batujajar 2) and Waduk Saguling was 10,0 μS. Whereas the TDS value of the water sample in Citarum River was 405 ppm (Batujajar 1) and 344 ppm (Batujajar 2) and Saguling Lake was 214 ppm. The TSS value of water sample in Citarum River was 180,4 ppm (Batujajar 1) and 163,9 ppm (Batujajar 2) and Saguling Lake was 75,1 ppm. The results of measurements of the physical parameters of the water sample in the two areas showed the value of TDS was under water quality standard (1000 ppm) and TSS value was above the water quality standard (50 ppm). The results of the water sample extraction in the two areas were characterized by GC (Gas Chromatography) and GC-MS (Gas Chromatography-Mass Spectrometry). The results of GC-MS in the water sample of Citarum River which is located in Batujajar showed there was not a possibility of extractable organic compounds in the solvent n-hexane. Whereas, there was a possibility of organic compounds which can be derived from impurities contained in solvent and organic compounds estimated from column C8. Whereas the results of GC-MS in the water sample of Saguling Lake indicated the possibility of organic compounds such as aroclor 5460, trans-beta-caryophyllene, butyl hydroxy toluene, mono (2-ethylhexyl) phthalate, 14-beta-h-pregna, and diisononyl phthalate respectively participated in the retention time 2,353 minutes, 8,617 minutes, 8,899 minutes, 9,075 minutes, 9,605 minutes, and 10,111 minutes.